2019
DOI: 10.1038/s41598-019-46518-9
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to maternal obesity during suckling outweighs in utero exposure in programming for post-weaning adiposity and insulin resistance in rats

Abstract: Exposure to maternal obesity during early development programmes adverse metabolic health in rodent offspring. We assessed the relative contributions of obesity during pregnancy and suckling on metabolic health post-weaning. Wistar rat offspring exposed to control (C) or cafeteria diet (O) during pregnancy were cross-fostered to dams on the same (CC, OO) or alternate diet during suckling (CO, OC) and weaned onto standard chow. Measures of offspring metabolic health included growth, adipose tissue mass, and 12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 54 publications
(81 reference statements)
1
24
0
Order By: Relevance
“…This interpretation is supported by the finding of Vogt et al, who could show that blockade of insulin signaling in hypothalamic anorexigenic POMC neurons protects the offspring from maternal HFD-induced malformation of POMC neuron projections (Vogt et al, 2014). It is important to note that increased hypothalamic insulin signaling at P21 in our model of maternal obesity seems to precede insulin resistance in the brain and peripheral organs in adult offspring as shown by previous work of our group (Schmitz et al, 2018) and others (Samuelsson et al, 2008; Akyol et al, 2012; Gomes et al, 2018; George et al, 2019). Thus, it is tempting to speculate whether adult-onset hypothalamic insulin resistance might be a functional consequence of increased hypothalamic insulin signaling during early life.…”
Section: Discussionsupporting
confidence: 64%
“…This interpretation is supported by the finding of Vogt et al, who could show that blockade of insulin signaling in hypothalamic anorexigenic POMC neurons protects the offspring from maternal HFD-induced malformation of POMC neuron projections (Vogt et al, 2014). It is important to note that increased hypothalamic insulin signaling at P21 in our model of maternal obesity seems to precede insulin resistance in the brain and peripheral organs in adult offspring as shown by previous work of our group (Schmitz et al, 2018) and others (Samuelsson et al, 2008; Akyol et al, 2012; Gomes et al, 2018; George et al, 2019). Thus, it is tempting to speculate whether adult-onset hypothalamic insulin resistance might be a functional consequence of increased hypothalamic insulin signaling during early life.…”
Section: Discussionsupporting
confidence: 64%
“…Additionally, it was found that CAF rats gained extra 22% in weight during the pre-pregnancy period compared to controls, and were heavier during pregnancy. Moreover, CAF diet-fed dams still remained heavier than animals fed a chow diet at mid-lactation 36 .…”
Section: Discussionmentioning
confidence: 95%
“…These non-significant effects may be a result of small groups in our study (n = 3 mothers/group). Indeed, studies on a bigger number of dams (n = 16/group) have shown that 6–13 weeks of exposure of rats to a CAF diet induced an increase in body weight in these animals 36 . Additionally, it was found that CAF rats gained extra 22% in weight during the pre-pregnancy period compared to controls, and were heavier during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…M-HF/HF had lower body weights early after weaning (3-9 weeks old), while their growth accelerated spontaneously at a later stage (10-15 weeks old). This was associated with metabolic complications including insulin resistance later in life 35 . While M-HF/HF had normal glucose tolerance at MID, they showed impaired glucose tolerance and insulin sensitivity, together with impaired insulin secretion activity and higher circulating level of PAI-1, at END.…”
Section: Discussionmentioning
confidence: 99%
“…Five μL of each dilution were introduced into the AscentisSi column (10 cm × 1 mm, 3 μm, Sigma-Aldrich, Darmstadt, Germany) with a flow rate of 50 μL min −1 . The temperature of the column oven was maintained at35 °C. The mass spectrometer with Orbitrap technology operated in positive (electrospray voltage 3.0 kV) and negative (electrospray voltage −2.7 kV) ion modes with a capillary temperature of 250 °C, a sheath gas flow of 15 U, a high resolution of 70 000 and AGC target 1e6.…”
mentioning
confidence: 99%